ACUTE AND SUB-ACUTE TOXICOLOGICAL ASSESSMENT OF THE AQUEOUS SEED EXTRACT OF PERSEA AMERICANA MILL (LAURACEAE) IN RATS - Ozolua, Raymond Iduojemu; Ogochukwu, Anaka N.; Okpo, S. O.; Idogun, S. E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The aqueous seed extract of Persea americana Mill (Lauraceae) is used by herbalists in Nigeria for the management of hypertension. As part of our on-going scientific evaluation of the extract, we designed the present study to assess its acute and sub-acute toxicity profiles in rats. Experiments were conducted to determine the oral median lethal dose (LD50) and other gross toxicological manifestations on acute basis. In the sub-acute experiments, the animals were administered 2.5 g/kg (p.o) per day of the extract for 28 consecutive days. Animal weight and fluid intake were recorded during the 28 days period. Terminally, kidneys, hearts, blood/sera were obtained for weight, haematological and biochemical markers of toxicity. Results show that the LD50 could not be determined after a maximum dose of 10 g/kg. Sub-acute treatment with the extract neither affected whole body weight nor organ-to-body weight ratios but significantly increased the fluid intake (P < 0.0001). Haematological parameters and the levels of ALT, AST, albumin and creatinine were not significantly altered. However, the concentration of total proteins was significantly increased in the treated group. In conclusion, the aqueous seed extract of P. americana is safe on sub-acute basis but extremely high doses may not be advisable.